Hubungan Kausalitas Antara Pertumbuhan Ekonomi, Indeks Pembangunan Manusia, Kemiskinan dan Pengangguran di Kabupaten Rokan Hulu - Wanda Hamidah; Isnaini Harahap; Khairina Tambunan (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research aims to find out the causal relationship between Economic Growth, Human Development Index, Poverty and Unemployment in Rokan Hulu Regency. This research is a quantitative research that uses Granger causality analysis tools. This analysis tool was chosen because its character is suitable for processing this research data in reveals the relationship between the variables studied. The data used is secondary data obtained through the official website of the Central Statistics Agency (BPS) of Riau Province and BPS of Rokan Hulu Regency. The type of data used is a time series, namely 2013-2020. From the results obtained, it can be explained that there is no significant influence between economic growth (EG), human development index (HDI), poverty (POV) and unemployment (UNEM) in the long term as shown in the results of the cointegration test. However, in the short term, there are UNEM variables from the previous period that have a positive and significant effect on current UNEM. From the results of the Granger Causality Test, there is no bidirectional causality from the human development index to economic growth. There is a one-way causality from poverty to economic growth. This means that economic growth has no effect on poverty, on the contrary, poverty has an effect on economic growth. There is no two-way causality from unemployment to economic growth. There is a one-way causality from poverty to the human development index. This means that the human development index has no effect on poverty, on the contrary, poverty has an effect on the human development index. There is a one-way causality from the human development index to unemployment. This means that unemployment has no effect on the human development index, on the contrary, the human development index has an effect on unemployment. There is a two-way causality from unemployment to poverty. This is shown by the probability values, each of which is greater than 0.05 (5%), so there is no causality between variables.